The Empirical Status of Empirically Supported Psychotherapies Assumptions, Findings and Reporting in Controlled Clinical Trials (Articles]. - Westen. Drew
The articles provides a critical review of the assumptions and findings studies used to establish psychotherapies as empirically supported. the attempt to identify empirically supported therapies (ESTs) imposes particular assumptions on the use of randomized controlled trial (RCT) methodology that appear to be valid for some disorders and treatment (notably exposure-based treatments of specific anxiety symptoms ) but substantially violated for others. Meta-analytic studies support a more nuanced view of treatment efficacy than implied by a dichotomous judgement of supported versus unsupported. The authors recommend changes in reporting practices to maximize the clinical utility of RCTs, describe alternative methodologies that maybe useful when the assumptions underlying EST methodology are violated and suggest a shift of validating treatment packages to testing intervention strategies and theories of change that clinicians can integrate into empirically informed therapies. -- (from the author